2020
DOI: 10.3389/fchem.2019.00931
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Chains: A Collaboration of Ubiquitin and Ubiquitin-Like Modifiers Introducing Cross-Functionality to the Ubiquitin Code

Abstract: The Ubiquitin CODE constitutes a unique post-translational modification language relying on the covalent attachment of Ubiquitin (Ub) to substrates, with Ub serving as the minimum entity to generate a message that is translated into different cellular pathways. The creation of this message is brought about by the dedicated action of writers, erasers, and readers of the Ubiquitin CODE. This CODE is greatly expanded through the generation of polyUb chains of different architectures on substrates thus regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 93 publications
(111 reference statements)
1
30
0
Order By: Relevance
“…Moreover, ubiquitin and certain Ubls, including SUMO, can form mixed chains, sometimes of complex and still ill-defined composition and topologies and can also be subjected to other post-translational modifications as discussed below. Elucidating the biochemical complexity and the biological consequences of what is now called the “ubiquitin code” is currently the object of intensive studies and still requires considerable efforts [ 33 , 34 , 35 , 36 ]. This implies that a number of conclusions from studies carried out before the advent of large-scale proteomics/modifomics might have to be reconsidered or, at least, nuanced.…”
Section: Sumoylation: a Principally Nuclear Post-translational Modmentioning
confidence: 99%
“…Moreover, ubiquitin and certain Ubls, including SUMO, can form mixed chains, sometimes of complex and still ill-defined composition and topologies and can also be subjected to other post-translational modifications as discussed below. Elucidating the biochemical complexity and the biological consequences of what is now called the “ubiquitin code” is currently the object of intensive studies and still requires considerable efforts [ 33 , 34 , 35 , 36 ]. This implies that a number of conclusions from studies carried out before the advent of large-scale proteomics/modifomics might have to be reconsidered or, at least, nuanced.…”
Section: Sumoylation: a Principally Nuclear Post-translational Modmentioning
confidence: 99%
“…Several reports show that NEDD8 forms chains in vitro and in vivo, although the function of polyneddylation is not well defined yet [10,78,[84][85][86]. In addition, clear experimental evidence demonstrated that, upon proteotoxic stress, proteins are simultaneously modified by NEDD8 and ubiquitin mixed-chains.…”
Section: The Nedd8 "Enigma"mentioning
confidence: 99%
“…☆ In contrast to ubiquitin and other ULMs, ISG15 and FAT10 comprises two ubiquitin-like domains joined by a flexible linker [ 61 ]. There is accumulating evidence showing that ubiquitin and ULMs could generate hybrid chains, which seem to confer improved specificity and affinity towards their cognate receptors and to diversify the “ubiquitin code” [ 62 ].…”
Section: Figurementioning
confidence: 99%